PERAN RASA SYUKUR TERHADAP KESEJAHTERAAN PSIKOLOGIS GURU HONORER TAMAN KANAK-KANAK DI JOMBANG - Jannah, Roudhotul; Chintya Dewi, Windy; Nursanti, Erma (IDEA: Jurnal Psikologi, 2024)
This research aims to determine the the role of gratitude on the psychological well being of honorary kindergarten teachers in Jombang. The Hypothesis porposed in thius reseacrh is that there is posivite relationship between psychologival well being and gratitude of honorary kindergarten teachers in Jombang. This research involved 72 honorary kindergarten teachers. This research uses product moments which are used to analyze data obtainerd using SPSS programs. The result of the hypothesis test there is a significant positive correlation between gratitude and psychological well being of honorary kindergarten teachers in Jombang.